KOLABORASI DALAM PENANGANAN COVID-19 PADA KEGIATAN KEAGAMAAN DI KOTA PEKANBARU TAHUN 2020 - Sherly Marshelinda; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Covid-19 (Corona Virus Disease) is a disease that was first reported in Wuhan City, China on December 31, 2019. The Covid-19 virus pandemic has also haunted Indonesia, including Pekanbaru City, because since the first cases it has been increasing. Covid-19 of course affects all aspects of life, especially in the field of religious activities because the spread of Covid-19 can pass through many crowds. To reduce the spread of Covid-19 through Perwako Pekanbaru Number 74 of 2020 concerning Guidelines for the Implementation of Social Restrictions in handling Covid-19 (Corona Virus Disease) in Pekanbaru City in order to improve community discipline. The purpose of this study is to describe Government Collaboration in handling Covid19 in religious activities in Pekanbaru City in 2020. This study uses the collaboration theory according to Noorsyamsa Djumara. The method used is descriptive qualitative as for the informants as many as 20 informants with 13 agencies, Pekanbaru City Bappeda as the main informant. Data collection techniques using interviews and documentation. Data analysis was carried out in this study through the stages of data reduction, data presentation, and conclusions. Based on the results of research on Collaboration in Handling Covid-19 in Religious Activities in Pekanbaru City that the collaboration of the Pekanbaru City government through 5 main components in Collaboration according to Noorsyamsa Djumara 2008 carried out by the Government is considered not optimal, the collaboration carried out in handling Covid-19 religious activities in Pekanbaru City consists of the religious sector Task Force teams. Keywords: Handling Collaboration, COVID-19, Religious Activities, Pekanbaru City.